A cleaner and one-step approach for robust coloration of polyester fibers via hydrophobic magnetically recoverable photocatalyst fatty acids/nano iron oxide coating. (20th January 2020) - Bashiri Rezaie, Ali; Montazer, Majid
Abstract: Recently, nanoparticles are applied broadly for nanocoloration of textiles as new class of colorants along with imparting diverse properties. However, lack of being environmentally friendly and feasible, having proper coloration properties such as good color fastness against rubbing, washing and acid spotting and being magnetically recoverable is perceived. Herein, we described a cleaner one-step approach for robust nanocoloration of polyester fibers via hydrophobic magnetically recyclable photocatalyst fatty acids/nano iron oxide coating for the first time. Introducing clean facile route as a possible replacement method of conventional textile coloration, eliminating hazardous dyes and auxiliaries, reducing textile effluents via using safe and magnetically recoverable colorant and photocatalytic dye degradation ability are the advantages of this route. A diverse color from light to dark brown with excellent color fastness ratings against washing, rubbing, acid and alkaline spotting and light was achieved for fabricated composites. Iron oxide nanoparticles along with fatty acids as safe coating not only improve the safety of the process but also enhance all the color fastness of the prepared samples along with forming very good hydrophobic behavior with water contact angle of 127 and 148°. The fabricated samples displayed proper magnetic feature with saturation magnetization of 1.69 emu/g at room temperature expressed the feasible and simple recovery of the possible released nanoparticles in waste water from washing. Appropriate photocatalytic performance (90.73%) towards discoloration of methylene blue after 48 h under daylight was also achieved. This route renders the idea of utilizing magnetic nanoparticles along with fatty acids for cleaner and facile nanocoloration of various fibers with multifunctional properties. Graphical abstract: Image 1 Highlights: Cleaner robust PET coloration by hydrophobic magnetic fatty acids/nano iron oxide. Introducing light to dark brown color on PET fibers with excellent color fastness. Exhibiting very good hydrophobic behavior with WCA of 127 and 148°. Feasibility of magnetically recovering with very good magnetic feature. Proper photocatalytic performance for degradation of methylene blue under daylight.